1989
DOI: 10.1039/f19898501315
|View full text |Cite
|
Sign up to set email alerts
|

A cubic equation of state for mixtures containing steam

Abstract: A cubic equation of state and combining rules for mixtures containing steam has been developed. The equation is based on the earlier equations of Clausius, Martin and Kubic, and contains two temperature-dependent parameters, which give it enough flexibility to fit the residual properties of both steam and non-polar fluids with sufficient accuracy. Mixture properties are calculated using pseudo-critical parameters for steam and a single temperature-independent interaction parameter { in the combining rule

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…These measurements interpolated to x=0.5 are plotted in figure 6 at the temperatures 573 K and 598 K. The continuous curves drawn through the points were calculated from the equation of state for the vapour phase used by Wormald et al (25) to fit their H E m measurements on (water+hydrocarbon). The temperatures 573 K and 598 K are above the critical temperature (562.1 K) of benzene and below the critical temperature (647.2 K) of water, and measurements in the vapour phase can be made at increasing pressures until the saturation pressure of the least volatile of the two fluids (water) is reached.…”
Section: Continuity With Vapour Phase H E M Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…These measurements interpolated to x=0.5 are plotted in figure 6 at the temperatures 573 K and 598 K. The continuous curves drawn through the points were calculated from the equation of state for the vapour phase used by Wormald et al (25) to fit their H E m measurements on (water+hydrocarbon). The temperatures 573 K and 598 K are above the critical temperature (562.1 K) of benzene and below the critical temperature (647.2 K) of water, and measurements in the vapour phase can be made at increasing pressures until the saturation pressure of the least volatile of the two fluids (water) is reached.…”
Section: Continuity With Vapour Phase H E M Measurementsmentioning
confidence: 99%
“…However, the fit to water is worst at low temperatures and improves at higher temperatures where the kinetic energy largely destroys the structuring effects due to hydrogen bonds, and it is of interest to see how well the equation compares with the measurements on (water+benzene). Parameters for the equation were determined from critical parameters in the usual way, (25) and an approximate fit to our measurements was obtained by adjusting the parameter k 12 in the equation …”
Section: Comparison With the Patel-teja Equation Of Statementioning
confidence: 99%
“…(1) were especially fitted to the volumetric properties of hydrocarbons, molar densities and enthalpies calculated from eqn. (1) for carbon dioxide using Kubic's generalised formulae for a( T), b and c( T ) are in good agreement with tabulated values. Molar densities of carbon dioxide calculated from eqn.…”
Section: + [B3 -3a(t)c(t)2/rt]/v: (2)mentioning
confidence: 99%
“…It was previously shown that measurements of the excess molar enthalpy H: for mixtures of steam with n-alkanes from methane to octane can be fitted using a cubic equation of state and one-fluid mixing rules. 'V2 The Kubic3 modification of the equation of state, (1) was used. This equation can be written as a series expansion similar to the virial equation of state, and the first four terms are,…”
mentioning
confidence: 99%
“…The a(T) terms were obtained from second virial coefficients of methanol and ethanol derived from flow calorimetric measurements of the excess molar enthalpy of the alcohol with nitr~gen,'.~ and the c(T) terms were determined by fitting eqn. (1) to saturated vapour densities. For methanol, a(T) and c(T), are given by the expressions a(T) = --923223, + 187395 + 305869Tr- ' + 98693, exp(3.763 Tr-I )…”
mentioning
confidence: 99%